Altruism, Gift and Symbolic Exchange : From Comte to Bourdieu - Steiner, Philippe (Social Sciences E-Books Online, Collection 2026., 2025)
Altruism, gifts and symbolic exchange refer to a vast set of practices deeply embedded in our market societies. They were successively theorized by Auguste Comte, Marcel Mauss, and Pierre Bourdieu. This book follows the outline of a history that has hitherto been glimpsed only as a series of fragments and which needs to be reassembled in order to see its full scope. This history is structured in terms of three stages: a critique of political economy, a theoretical construction backed by empirical practices, and, finally, an assessment of the social effects of the dissemination of economic knowledge.